ダイ 8 ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1966 1967 - 楠, 宏; クスノキ, コウ; KUSUNOKI, Kou (国立極地研究所, 1967)
P(論文) Fourty members of the 8th Japanese Antarctic Research Expedition left Tokyo on December 1, 1966, aboard the icebreaker FUJI The expedition was led by Tetsuya TORII, also leading the wintering party consisting of 24 men, and the author, as deputy-leader, led the summer party of 16 men. On December 22, 1966, the FUJI, under the command of Captain Mitsutoshi MATSUURA, left Fremantle, Western Australia, for Syowa Station, with 182 officers and crew, 40 expedition members, three observers including one American glacial-geologist, and 3 news media personnel. The FUJI carried 460 tons of cargo and was equipped with two Sikorsky S-61A helicopters and one Bell 47GA helicopter. On January 4, 1967, the FUJI reached the ice edge in the offing of the Enderby Land and proceeded southwestward along the edge of fast ice developed along the coast of the Prince Olav Land. On January 7 four flights of helicopters to Syowa Station were made carrying advance personnel and cargo, when the ship anchored at the edge of fast ice, about 50 nautical miles north of the station On the 14th, the ship approached the station and anchored within one kilometer east of the station near the northeast tip of the East Ongul Island Unloading of about 460 tons of materials was finished on the 26th, of which about 30 tons of heavy vehicles and other materials were transported over ice. Oil barrels, building panels, and heavy items were airlifted by underslung cargo net. Fuel for diesel generators was delivered in bulk by means of removable cabin tank in one helicopter in a later period of resupply operation On February 6, the FUJI left the station, taking the same route, and reached the edge of fast ice on the 8th. Eight men of the 8th summer party and 4 men of the 7th wmter-overed party were left at the station to accomplish remaining task. At the noon of February 10, the station was officially turned over to the 8th wintering party, under the witness of Akira MUTO, leader of the 7th wintering party, Captain MATSUURA, and the author. At the ...